Perceptions of Online University Students Toward Artificial Intelligence Integration in Medical Education and Decision-Making: A Multi-Faculty Survey Study in Afghanistan - Mohammad Nawab Turan; Pashtana Amiry; Khudai Qul Khaliqyar (Current Educational Review, 2026)
The integration of artificial intelligence (AI) into education has emerged as a transformative force reshaping pedagogical approaches, decision-making processes, and learning outcomes across disciplines. In Afghanistan, where the higher education system is navigating unprecedented digital transformation amid resource constraints and post-conflict reconstruction, understanding student perceptions of AI adoption is critically important. This cross-sectional survey study investigated the attitudes, awareness, perceived usefulness, and behavioral intentions of online university students across six faculties at the Vision Online University of Afghanistan toward AI integration in medical and general higher education. A structured, validated questionnaire was administered to 384 purposively sampled students from the Faculties of Medicine, Engineering, Law, Education, Natural Sciences, and Business Administration. Data were collected between March and June 2024 and analyzed using descriptive statistics, one-way ANOVA, and structural equation modeling. Results indicated that overall awareness of AI was moderately high (M = 3.72, SD = 0.84 on a 5-point Likert scale), with Medical Faculty students reporting significantly higher perceived usefulness (M = 4.01) compared to Law (M = 3.45) and Business (M = 3.90) faculties (F(5,378) = 4.83, p < .001). Students broadly favored AI-assisted clinical decision support and adaptive learning tools. Key barriers included limited digital infrastructure, inadequate AI literacy training, and language-related concerns specific to Dari and Pashto speakers. The findings provide empirical grounding for a faculty-differentiated AI integration strategy in Afghan higher education